Habitus transition experience among Yemeni Community leaders in Malaysia: a literature review and philosophical rationale - Al-Bahri, Nabil Mohsen; Sabra, Mohammad Shatar; Abdullah, Amini Amir; Gill, Sarjit S. (Middle Eastern Muslim Graduates Association Press, 2018)
This study explores the habitus transition experience of the Yemeni Community leaders in Malaysia (YCM leaders) and how this experience affected their perspectives, beliefs, behaviors and practices of community leadership and social disposition. The purpose of this study is to; interpret how YCM leaders transit their habitus of community leadership from Yemeni Sheikh perspective and behavior to the Malaysian Datoones, how they learn from the local community how to develop their strategies and schemes for social disposition and community leadership. It investigated also, how YCM leaders’ build-up their self-efficacy beliefs about their capabilities and skills to exercise leadership, how they observe and replicate the local model of community leader. Also, the study tried to explain how YCM women leaders develop their perception of their social disposition. The study has utilized the qualitative method that included participants’ observation of YCM leaders and semi-structured interviews to the 12 YCM leaders who have been living in Malaysia for more than five years and who have played leadership roles among the YCM. The findings demonstrated that YCM leaders have been transiting their community leadership habitus from the Yemeni socio cultural norms of community leadership and social disposition to the Malaysian ones. YCM have been transiting from the Yemeni Sheikhs style of community leadership to the Malaysian Dato ones which influenced their leadership perspective and practices. It found that the habitus transition of YCM leaders regarding pursuing social disposition and exercising community leadership based on accumulating ‘capitals’ as a way of maximizing their self-efficacy as community leaders. It found also, that YCM leaders observe and imitate the local model of community leadership. For the female participants, the study demonstrated that even though that YCM women leaders show development in their persuasion for social disposition, they have achieved the level of participation because of many factors. This idea may enhance and develop Yemeni students’ and community leaders’ understanding about the perspective and practices of community leadership according to the local style. YCM educational council may initiate programs for educating and training the next generation about fair and normative social contracts and arrangements that create peace and harmony among the socially and socio-politically unstable Islamic societies such as of Yemen. The outcomes of this research have emerged to contribute in bridging the gap that has existed theory and practice of community leadership development.